A comparison between the structure in elite tennis and kids tennis on scaled courts (Tennis 10s) - Schmidhofer, S.; Leser, R.; Ebert, M. (International Journal of Performance Analysis in Sport, 2014)
This study aimed to compare the playing structure between ATP tennis and three different kids age groups following the ITF's "Tennis 10s" concept. The playing structure was defined by means of 17 conventional performance parameters. All in all 48 matches were analysed by proper video footage. Sixty-seven different players participated in the study. The ATP group comprised a mixture of different player types (offensive/defensive base line players, serve and volley players etc.) competing in the round of 16 matches up to finals in official ATP tournaments. The kids sample consisted of the best 20 Austrian players from the age groups Boys Under 9 (U9), Under 10 (U10) and Under 12 (U12). Absolute and relative differences as well as one-way ANOVA were calculated between the groups. The study's results indicate that the playing structure of the U9 is most similar to ATP tennis among all youth groups, followed by the U12 and the U10. While the age groups U12 and U10 are playing on a full size court the age group U9 is the only one playing on a scaled court (Orange-Court). This obviously affects the technical and tactical playing style being closer to adult tennis compared to the other groups. In particular evident was the problem of a too large field (full size court) for the U10. Although taller and physically stronger, their performance parameters differentiated much more from ATP tennis than the U9 ones.